PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS SOSIAL KOTA DEPOK - Silsilia Febriani; Esti Suntari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to determine the influence of physical work environment and work discipline on the performance of Depok City Social Service employess both partially and simultaneously. The research method used is the quantitative method. The population in this study is employees at the Depok City Social Service which amounted to 52 people with a saturated sample number so the population used was all employees of the Depok City Social Service as many as 52 respondents. Data collection techniques by distributing questionnaires. The data analysis method used simple and multiple linear regression tests, correlation coefficients, determination coefficients, partial t tests and simultaneous tests f. The results of this study show that: there is a positive and significant influence between the physical work environment on the performance of Depok City Social Service employees, this is evidenced by the results of simple linear regression of Y = 19.926 + 0.546 X1, the value of the correlation coefficient is 0.617 (strong),  The value of the determination coefficient was 38.0%, and the t-value was calculated 5.537 > t table 2.009 with a significant value of 0.000 < 0.05. There is a positive and significant influence between work discipline on the performance of Depok City Social Service employees, this is evidenced by the results of a simple linear regression of Y = 8.243 + 0.801 X1, a correlation coefficient value of 0.701 (strong), a determination coefficient value of 49.1%, and a calculated t value of 6.945 > t table 2.009 with a significant value of 0.000 < 0.05. Simultaneously there is a positive and significant influence between the work environment and work discipline on the performance of Depok City Social Service employees, this is evidenced by the results of multiple linear regression of Y = 8.151 + 0.191 X1 + 0.618 X2, the correlation coefficient value of 0.715 (strong), the determination coefficient value of 51.2%, and the f-value of 25.695 > f of table 3.187 with a significant value of 0.000 < 0.05.